PENGARUH KEMAMPUAN PUBLIC SPEAKING TERHADAP KEPERCAYAAN DIRI MAHASISWA PGSD - Rahmawati, Rahmawati; Muchliza Zahra, Andi; Putri Juanda, Aulia; Nurhaeda, Nurhaeda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Public speaking is a crucial communication skill for PGSD students as future educators, yet many students still face obstacles such as anxiety and low self-confidence. This study aims to empirically determine the effect of public speaking skills on the self-confidence of PGSD students. This study used a quantitative approach with a correlational or causal research type on 22 PGSD students at Makassar State University who were selected using a purposive sampling technique. Data collection techniques were carried out by distributing questionnaires using Google Forms which were then analyzed statistically using descriptive analysis, the Shapiro-Wilk normality test, and simple linear regression analysis. The results showed that the data were normally distributed, but the regression test produced a significance value of 0.997 (> 0.05) with a regression coefficient value of 0.001. Based on these results, it can be concluded that public speaking skills do not have a significant effect on the self-confidence of PGSD students in this study. This low influence indicates that student self-confidence is likely more influenced by other internal and external factors, such as psychological conditions, personal experiences, and social environmental support.